Drivers and Moderators of Social Media-Enabled Cooperative Learning in Design Education: An Extended TAM Perspective from Chinese Students - Tiansheng Xia; Yujiao Wu; Yibing Chen (Behavioral Sciences)
This study aims to explore the mechanisms through which social media influences the cooperative learning attitudes and academic performance of design students in the context of China’s collectivist culture, providing a basis for the application of social media in design education. Using the Extended Technology Acceptance Model (TAM) as the theoretical framework, a questionnaire survey of 305 students was conducted. Structural equation modelling and moderation effect analysis revealed that perceived usefulness, ease of use, enjoyment, and interactivity significantly influence students’ attitudes toward social media-based collaborative learning. This attitude directly enhances academic performance and is positively moderated by knowledge-sharing willingness and academic self-efficacy. This study validated the applicability of the extended TAM in online collaborative learning, revealing that positive attitudes toward collaborative learning can only effectively translate into academic outcomes when students possess sufficient knowledge-sharing willingness or self-efficacy. This provides empirical evidence for strategically leveraging social media in educational design.